Lightweight Thread Tunnelling in Network Applications - Donnelly, Austin (Proceedings of the IFIP-TC6 4th International Working Conference on Active Networks (IWAN'02), 2002)
Active Network nodes are increasingly being used for nontrivial processing of data streams. These complex network applications typically benefit from protection between their components for fault tolerance or security. However, fine-grained memory protection introduces bottlenecks in communication among components. This paper describes memory protection in Expert, an OS for programmable network elements which re-examines thread tunnelling as a way of allowing these complex applications to be split over multiple protection domains. We argue that previous problems with tunnelling are symptoms of overly general designs, and we demonstrate a minimal domain-crossing primitive which nevertheless achieves the majority of benefits possible from tunnelling.